NILAI-NILAI PERMAINAN TRADISIONAL BANJAR ‘BAHAGAAN’ SEBAGAI SUMBER PEMBELAJARAN IPS SD NEGERI 3 GUNTUNG MANGGIS - Hilyatul Mahmudah (Universitas Lambung Mangkurat, 2018)
AbstractEducation succeeds if it shows changes in the behavior of learners towards the better. Definitive behavioral changes begin with positive values of education. Values are considered as one of the factors that support a person's behavior to act good or bad, right or wrong. The value of the character must be developed during the learning process, one way of developing can be through traditional games. Traditional games are more fun and well liked by learners making it easier to instill values that can make good behavior. Traditional Banjar 'bahagaan' games are considered to foster character values in education through social studies learning resources. The aim of the study was to describe Banjar 'bahagaan' traditional game, explaining the stages of traditional Banjar 'bahagaan' game and describes the traditional Banjar 'bahagaan' game values as learning resources for social studies. The research method used is qualitative research. Data collection techniques used observation, interview and documentation study. The result of the research is the value obtained from the traditional game Banjar 'bahagaan' is the students can describe the traditional game Banjar 'bahagaan' and explain the stages of the game in detail and complete then learners are able to show the cooperation, togetherness and friendship that gave rise to the values self-esteem that can be a source of social studies learning that is religious value, honest value, tolerance value, discipline value, hard work value, democratic value, spirit value, the value of responsibility and the value of curiosity. Suggestions from the research is the need to socialize the use of traditional games Banjar 'bahagaan' as a means of learning and improvement in order to be innovative learning in teaching and learning activities of social studies with support from schools related facilities facilities and infrastructure learning.Keywords: Traditional game, values, social studies, and learning resources AbstrakPendidikan berhasil jika memperlihatkan perubahan perilaku peserta didik kearah yang lebih baik. Perubahan perilaku pasti di awali dengan nilai-nilai yang positif dari pendidikan. Nilai dianggap sebagai salah satu faktor yang mendukung perilaku seseorang untuk bertindak baik atau buruk, benar atau salah. Nilai karakter harus dikembangkan saat proses pembelajaran, satu cara mengembangkan dapat melalui permainan tradisional. Permainan tradisional lebih menyenangkan dan disukai peserta didik sehingga lebih mudah menanamkan nilai-nilai yang dapat membuat perilaku yang baik. Permainan tradisional Banjar ‘bahagaan’ dianggap dapat menumbuhkan nilai-nilai karakter dalam pendidikan melalui sumber pembelajaran IPS. Tujuan penelitian untuk mendeskripsikan permainan tradisional Banjar ‘bahagaan’, menjelaskan tahapan permainan tradisional Banjar ‘bahagaan’ dan menguraikan nilai-nilai permainan tradisional Banjar ‘bahagaan’ sebagai sumber pembelajaran IPS. Metode penelitian yang digunakan adalah penelitian kualitatif. Teknik pengumpulan data menggunakan observasi, wawancara dan studi dokumentasi. Hasil dari penelitian yaitu nilai yang didapatkan dari permainan tradisional Banjar ‘bahagaan’ adalah peserta didik dapat mendeskripsikan permainan tradisional Banjar ‘bahagaan’ serta menjelaskan tahapan-tahapan permainan secara rinci dan lengkap kemudian peserta didik mampu menunjukkan kerjasama, kebersamaan dan persahabatan yang memunculkan nilai-nilai karakter pada diri sendiri yang dapat menjadi sumber pembelajaran IPS yaitu nilai religius, nilai jujur, nilai toleransi, nilai disiplin, nilai kerja keras, nilai demokratis, nilai semangat kebangsaan, nilai menghargai, nilai bersahabat/komunikatif, nilai cinta damai, nilai peduli sosial, nilai tanggung jawab dan nilai rasa ingin tahu. Saran dari penelitian adalah perlu adanya sosialisasi pemanfaatan permainan tradisional Banjar ‘bahagaan’ sebagai sarana belajar serta peningkatan agar dapat menjadi inovasi pembelajaran dalam kegiatan belajar mengajar pendidikan IPS dengan dukungan dari sekolah terkait fasilitas sarana dan prasarana pembelajaran.Kata Kunci: Permainan tradisional, nilai, IPS, dan sumber belajar